The impact of type 2 diabetes mellitus on the clinical profile, myocardial fibrosis, and prognosis in non-ischemic dilated cardiomyopathy: a prospective cohort study - Yangjie Li; Hong Xian; Yuanwei Xu; Weihao Li; Jiajun Guo; Ke Wan; Jie Wang; Ziqian Xu; Qing Zhang; Yuchi Han; Jiayu Sun; Yucheng Chen (Cardiovascular Diabetology, 2024)
Abstract Background The impact of the coexistence of type 2 diabetes mellitus (T2DM) in patients with non-ischemic dilated cardiomyopathy (DCM) on clinical profiles, myocardial fibrosis, and outcomes remain incompletely understood. Method A total of 1152 patients diagnosed with non-ischemic DCM were prospectively enrolled from June 2012 to October 2021 and categorized into T2DM and non-T2DM groups. Clinical characteristics, cardiac function, and myocardial fibrosis evaluated by CMR were compared between the two groups. The primary endpoint included both all-cause mortality and heart transplantation. Cause of mortality was classified into heart failure death, sudden cardiac death, and non-cardiac death. Cox regression analysis and Kaplan-Meier analysis were performed to identify the association between T2DM and clinical outcomes. Propensity score matching (PSM) cohort including 438 patients was analyzed to reduce the bias from confounding covariates. Results Among the 1152 included DCM patients, 155 (13%) patients had T2DM. Patients with T2DM were older (55 ± 12 vs. 47 ± 14 years, P < 0.001), had higher New York Heart Association (NYHA) functional class (P = 0.003), higher prevalence of hypertension (37% vs. 21%, P < 0.001), atrial fibrillation (31% vs. 16%, P < 0.001), lower left ventricular (LV) ejection fraction (EF) (23 ± 9% vs. 27 ± 12%, P < 0.001), higher late gadolinium enhancement (LGE) presence (55% vs. 45%, P = 0.02), and significantly elevated native T1 (1323 ± 81ms vs. 1305 ± 73ms, P = 0.01) and extracellular volume fraction (ECV) (32.7 ± 6.3% vs. 31.3 ± 5.9%, P = 0.01) values. After a median follow-up of 38 months (interquartile range: 20–57 months), 239 patients reached primary endpoint. Kaplan-Meier analysis showed that patients with T2DM had worse clinical outcomes compared with those without T2DM in the overall cohort (annual events rate: 10.2% vs. 5.7%, P < 0.001). T2DM was independently associated with an increased risk of primary endpoint in the overall (Hazard ratio [HR]: 1.61, 95% CI: 1.13–2.33, P = 0.01) and PSM (HR: 1.54, 95% CI: 1.05–2.24, P = 0.02) cohorts. Furthermore, T2DM was associated with a higher risk of heart failure death (P = 0.006) and non-cardiac death (P = 0.02), but not sudden cardiac death (P = 0.16). Conclusions Patients with T2DM represented a more severe clinical profile and experienced more adverse outcomes compared to those without T2DM in a large DCM cohort. Trial registration Trial registration number: ChiCTR1800017058; URL: https://www.clinicaltrials.gov .